Epiregulin expression and secretion is increased in castration-resistant prostate cancer - Wiesehöfer, Marc; Raczinski, Benedikt Bernhard Gereon; Wiesehöfer, Caroline; Dankert, Jaroslaw Thomas; Czyrnik, Elena Dilara; Spahn, Martin; Kruithof-de Julio, Marianna; Wennemuth, Gunther (Frontiers in Oncology, 2023)
In prostate cancer, long-term treatment directed against androgens often leads to the development of metastatic castration-resistant prostate cancer, which is more aggressive and not curatively treatable. Androgen deprivation results in elevated epiregulin expression in LNCaP cells which is a ligand of EGFR. This study aims to reveal the expression and regulation of epiregulin in different prostate cancer stages enabling a more specific molecular characterization of different prostate carcinoma types. An increased epiregulin secretion is detected in castration-resistant prostate cancer cell lines and prostate cancer tissue samples indicating a correlation of epiregulin expression with tumor recurrence, metastasis and increased grading. Analysis regarding the activity of different transcription factors suggests the involvement of SMAD2/3 in the regulation of epiregulin expression. In addition, miR-19a, -19b, and -20b are involved in post-transcriptional epiregulin regulation. The release of mature epiregulin occurs via proteolytic cleavage by ADAM17, MMP2, and MMP9 which are increased in castration-resistant prostate cancer cells. The results demonstrate epiregulin regulation by different mechanism and suggest a potential role as a diagnostic tool to detect molecular alterations in prostate cancer progression. Additionally, although EGFR inhibitors false in prostate cancer, epiregulin could be a therapeutic target for patients with castration-resistant prostate cancer.